Singapore's Ageing Population : Managing healthcare and end-of-life decisions - Chan, Wing-Cheong (Abingdon, Oxon : Routledge, 2011)
'A rapidly ageing population is the most significant demographic issue confronting Singapore in our lifetime. This has created new and increasing demands on Singapores healthcare system and on the families of the older adults. The challenge is in providing a system of care that is humane, effective and sustainable financially. This requires coordination between state funded providers, the family and the community. This book offers a multi-disciplinary perspective by researchers from various disciplines such as medicine, sociology, anthropology and law on managing healthcare and end of life decisions in Singapore. Providing information and suggestions for better policy formulation towards the aged this book is an invaluable resource for policy makers, service practitioners and scholars working on Asian gerontology and health and social policy more generally'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Older people -- Medical care -- Singapore; Health Services for the Aged -- organization & administration -- Singapore; Aged -- Singapore; Decision Making -- Singapore; Long-Term Care -- methods -- Singapore; Terminal Care -- methods -- Singapore; Terminally Ill -- Singapore